Swimming in the spaghetti bowl : challenges for developing countries under the 'new regionalism' - Majluf, Luis Abugattas (UN New YorkUS, 2004)
Looks at the main features characterizing the new regionalism. Highlights some of the major challenges confronting developing countries, which emerge from the interface between the new regionalism and events taking place in the multilateral trading system. Focuses on the issue of regionalism and trade in services, analyzing some of the main issues that should be addressed in the ongoing negotiations in the WTO.